2015
DOI: 10.1155/2015/641415
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Cd, Zn, and Pb from Soil Treated by Limestone with Variation of pH Using a Column Test

Abstract: Decades of mining in South Korea have resulted in the contamination of large amounts of soil by metals. The most feasible approach to site restoration requires the use of a stabilization agent to reduce metal mobility. This study examined the leaching characteristics of limestone used as a stabilization agent when subjected to solutions of differing pH. In a laboratory-scale column test, solutions with pH values of 3.5, 4.6, and 5.6, representing acidic to nonacidic rainfall, were applied to soil mixed with li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 25 publications
(30 reference statements)
2
4
0
Order By: Relevance
“…However, neutral pH (7) significantly reversed the toxicity of Cd in wheat seedlings by improving growth and leaf area, chlorophyll and carotenoids contents, macro, and micronutrients availability, enzymatic and non-enzymatic antioxidative defense systems activities, declining Cd contents, MDA, H 2 O 2 , and EL contents as compared to both acidic (5) and alkaline pH (9). These results are in line with former findings [ 10 12 , 41 , 42 ]. The recorded data demonstrated that both extreme pH levels rather than neutral caused a significant reduction in physiological traits, and thus, these pH levels were supposed as stress in wheat seedlings.…”
Section: Discussionsupporting
confidence: 94%
“…However, neutral pH (7) significantly reversed the toxicity of Cd in wheat seedlings by improving growth and leaf area, chlorophyll and carotenoids contents, macro, and micronutrients availability, enzymatic and non-enzymatic antioxidative defense systems activities, declining Cd contents, MDA, H 2 O 2 , and EL contents as compared to both acidic (5) and alkaline pH (9). These results are in line with former findings [ 10 12 , 41 , 42 ]. The recorded data demonstrated that both extreme pH levels rather than neutral caused a significant reduction in physiological traits, and thus, these pH levels were supposed as stress in wheat seedlings.…”
Section: Discussionsupporting
confidence: 94%
“…Because mobility and adsorption preference are inversely related, Pb has a lower mobility than Zn and Cd, which explains why Pb hotspots occurred much closer to the mine than Zn and Cd hotspots. is finding is consistent with the results of column leaching tests performed in other studies, which suggest that the Pb concentration in leaching solutions is very low, even in mining-impacted soil containing high concentrations of Pb [62][63][64].…”
Section: Journal Of Chemistrysupporting
confidence: 92%
“…Acid rain lowers the soil pH and increase metal mobility in the soil [92]. Acid rain is caused by volcanic activity, fossil fuel emissions, wildfi res and lightning and has been reported in several countries including USA and South Korea [93]. This acidic input may further exacerbate metal pollution and cause leaching in agricultural soils.…”
Section: Environmental Conditions: Environmental Conditions Suchmentioning
confidence: 99%